Squeeze Casting of Semiolid A356 Alloy - Xiang-Jie Yang (Advances in Mechanical Engineering, 2014)
The rheo-squeeze casting (rheo-SQC) combining the rheocasting and the SQC was developed, in which semisolid slurry was produced by the low superheat pouring with a shearing field (LSPSF) process. The three-dimensional morphology of the primary α-Al phase and the rest spacing of slurry prepared by LSPSF process have been reconstructed and visualized, and the microstructures of squeeze cast A356 alloy have been obtained. Based on the three-dimensional microstructure reconstructed, their three-dimensional characterizations such as solid volume fraction and equivalent diameter of the extracted primary α-Al phase of the slurry were measured and calculated. And the microstructures of cross-section of squeeze cast product were investigated. Compared and analyzed the typical microstructure characteristics of parts in different positions produced by SQC and rheo-SQC, the results show that the primary α-Al phase was in the form of enriched dendrites across the whole section of parts produced by SQC. Nevertheless, in the relative case of the rheo-SQC, the whole formations of dendrites have been inhibited effectively, revealing a conspicuous modification in morphology and refinement of the primary α-Al phase. In addition, the solid fraction decreased from the centre to the verge of products along the slurry flow orientation.